Wi-Fi networks in small and medium-sized businesses (SMB) - Sojak, Mariusz; Głowacki, Szymon (Studia Informatica. System and information technology, 2009)
Wi-Fi is quite a new technology on the market. This paper’s aim was to prove the justifiability and profitability of this technology use in the small and medium-sized businesses sector. Advantages and disadvantages of this kind of network were also shown. An issue connected with data and configuration elements security was also raised. Other wireless technologies were also presented.